PERILAKU KEPEMIMPINAN, MOTIVASI KERJA DAN KINERJA - Febri Yuliani, Abukari, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Leadership Behavior, Work Motivation and Performance. The purpose of this studywas to determine and analyze the influence of leadership behavior and work motivation of schoolprincipals with teacher performance in State Junior High Schools in Tambang District, KamparRegency. This research was conducted on teachers at State Junior High Schools who served inTambang District with a population of 262 teachers, consisting of 7 schools with a sample of 149teachers. This research is quantitative research. Data collection techniques are interviews, anddocumentation. Analysis of multiple regression data. The results showed that the leadershipbehavior and work motivation of school principals had a significant effect on the performance ofteachers in state junior high schools in Tambang Subdistrict, Kampar District, with a percentage of65.2% and the remaining 34.8% influenced by other variables not included in this regressionmodel. Based on linear regression Y = 62,690 + 0,131 Leadership Behavior + 0,444 WorkMotivation + e shows that the variable that most influences on teacher performance is workmotivation variable which is 60.7% and leadership behavior variable is only 57.6%.